Dalla psicoterapia individuale a quella di gruppo Appunti di controtransfert - Del Bianco, Vilma (Il sogno della farfalla, 2005)
The scope of this article is to explore the passage from individual to group psychotherapy. The starting point is a reflection on the nature of organic medicine which features a dual relationship between doctor and patient which becomes evident when we pass from “ taking care” of a patient to “curing” him. The article presents a description of a personal experience, as well as a number of clinical cases. The personal formation of the psychotherapist emerges as a fundamental element for group therapy; at the same time we are able to witness the presence in it of a number of additional therapeutic instruments in respect to individual psychotherapy, which leads us to think that the former is more effective from a therapeutic point of view. After considering Massimo Fagioli's theory and practice, we are able to formulate the hypothesis that in psychiatry, the passage from “taking care of” to “curing” happens with the advent of group therapy.